Odpowiedzi

2010-02-05T16:02:27+01:00
A) 6 x (-9) = -54
b) (-4) x ½ = -2
c) (-10) x 1,5 = -15
d) (-2/3) x (-2/5) = 4/15
e) (-18) : 3 = -6
f) 2,2 : (-2) = -1,1
g) 0,8 x (-5) = -4
h) (-9) x (-2/3) = 18/3 = 6
i)(-3) : (-1/3) = 27/3 = 9
1 5 1
2010-02-05T16:04:15+01:00
A) -54
b) -2
c) -15
d) cztery piętnaste
e) -6
f) -1,1
g) -0,45
h) 6
i) 9

; ))
2010-02-05T16:06:29+01:00
A) 6*(-9)= -54
b) (-4)*½ = -2
c) (-10)*1.5= - 15
d)- ²/₃* (-²/₅)= -⁴/₁₅
e) (-18):3= -6
f) 2.2:(-2)= -1,1
g) 0.8*(-5)= -4
h) (-3:(- ½)=-6
i) (-3:(-¹/₃)= 9